D-Dimer Serum Level Association With Mortality In Acute Stroke Patiens With Covid-19 - Moch Syahrial Pramudia Tarmidi; Nurul Fitria; Oryzasativa Giovanni; Akhdan Zharfan Puspito; Sintia Wahyu Arifah; Gibran Maulana Akbar (Saintika Medika)
Background: Since WHO declared COVID-19 a pandemic, Indonesia, including RSUD Gambiran Kediri, has experienced a sharp increase in morbidity and mortality. The global incidence of acute stroke in COVID-19 patients is 1.4%, with symptoms varying from mild to severe, including death. Elevated serum D-dimer in COVID-19 patients can be a biomarker to predict severe complications.